Novel Hydroxylated Cardanol Quaternary Ammonium Salts from Renewable Resource and its Synergistic Vesicles of Binary and Ternary Composite System in Detergent. Issue 1 (28th July 2020) - Zhao, Xuehua; Lv, Jinge; Wang, Limin; Han, Jianwei
Abstract: A series of novel hydroxylated cardanol quaternary ammonium salts (HCQAS 3a–3g) with one or two hydroxyl groups, derived from renewable cardanol, a plant‐based and low‐cost material natural cashew nut shell liquid (CNSL), have been rationally designed and investigated as additive in detergent. CMC, γ CMC, C20, pC20, and CMC/C20 were employed to exhibit the surface properties of HCQAS, reflecting that the surfactivity were superior to general cationic surfactants. In addition, HCQAS revealed excellent water solubility and wettability by krafft point and contact angle tests. Moreover, emulsifiability and foamability conversions were monitored versus time and volume of foam, respectively. Also, TEM micrographs were taken to provide the aggregation morphologies of HCQAS 3a aqueous solution at different concentration. Furthermore, HCQAS 3a and BGF‐10 binary composite system as well as HCQAS 3a, BGF‐10, and SDBS ternary composite system were investigated by CMC, γ CMC, emulsifiability, and foamability to determine the optimum molar ratio (HCQAS 3a: BGF‐10: SDBS = 0.24:0.36:0.4), and then, analysis of morphology by TEM showed that the incorporation of HCQAS 3a, BGF‐10, and SDBS in aqueous solution accelerated the formation of abundant vesicles with large volume and surface area. Finally, a green concentrated detergent was designed and prepared with the filtered ratio, where the presence of vesicles greatly enhanced detergency to promisingly replace the familiar use of petroleum‐based TX‐10 in detergent. This study on the structure and performance of HCQAS may shed some light on the development of novel environmentally friendly surfactant.